Digital Marketing Application through Marketing Strategy for Solo Meatballs in Malang - Daniel Ayub Dawan,; Aurelia Hayati Halim, (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
Numerous difficulties have been brought up by the COVID-19 epidemic, particularly for offenders and MSMEs. SMEs appear to be forced to adapt to these developments due to the transition from offline to online marketing. According to Ministry data, just 13% of all SMEs, or over eight million business operators, are currently able to use information technology in their operations. The goal of this study is to learn more about Bakmi's use of digital marketing in Tando 07 and the challenges that it encounters. This study employs qualitative approaches such as structured interviews, in-depth interviews, and business actors' observations. According to the study's findings, digital marketing entails updating product statuses on social media platforms like Facebook, Instagram, and WhatsApp. In order to expand the ease of food delivery and add online product marketing platforms, it also developed relationships with Go-Food, Grab-Food, and Shopee-Food. Digital marketing implementation challenges include a shaky internet connection, supply delays, and internal issues brought on by a lack of staff due to the high demand brought on by social media advertisements.